The influence of the ovarian-menstrual cycle phases on the psychological functioning of female athletes - Shan, M.; Kozhedub, M.; Vrublevskiy, E. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the dynamics of subjective assessment of the psychofunctional state of female athletes of various specialisations throughout the ovarian-menstrual cycle.